Chiral amino-acid-amide based ionic liquids as a stereoselective organocatalyst in asymmetric transfer hydrogenation of acetophenone at room-temperature - Javle, Balasaheb R.; Kinage, Anil K. (Chemistryselect, 2018)
Chiral Ionic Liquids (CILs) of amino acid amide were synthesized and used as novel organo catalyst for Asymmetric Transfer Hydrogenation (ATH) of acetophenone at room temperature. The developed CILs show very high yield and excellent enantio-selectivity in transfer hydrogenation of acetophenone.